Inclusive Education Policy in Madrasah - Ricka Tesi Muskania (AT-TURATS, 2022)
Inclusive education is an educational reform for children with special needs so that they have the same rights to obtain an education. This policy of inclusive education is increasingly being promoted with the perception that all Indonesian citizens have the same rank as the fulfillment of human rights in all aspects of life. This study aims to describe policies related to inclusive education in madrasah under the auspices of the Ministry of Religion. This research is a literature study that analyzes the ministry of religion's policies related to inclusive education. The results of the literature study show that inclusive education policies in madrasah are still limited to normative and regulatory policies. The implementation of the policy has not been supervised by all madrasah at the primary education level (Madrasah Ibtidaiyah), and secondary education (Madrasah Tsanawiyah and Madrasah Aliyah).